Preparation method of composite fireproof door core

By combining straw coated with calcium phosphate for flame retardancy with cement-based powder, expanded vermiculite, and hydrogen peroxide foaming process, a composite fireproof door core with excellent fireproof and heat insulation performance, high mechanical strength, and lightweight characteristics is prepared. This solves the problem of balancing material lightweighting with strength and fire resistance in existing technologies, and achieves high strength and fire safety reliability for the fireproof door core.

CN121470889APending Publication Date: 2026-02-06ZHONGSHAN FUMEN WOOD PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511672880.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing fire door core materials struggle to balance lightweight design with strength and fire resistance. Traditional materials are also prone to damage during transportation, installation, and use, affecting fire safety and reliability.

Method used

A composite fireproof door core is prepared by combining straw coated with calcium phosphate for flame retardancy with cement-based powder, expanded vermiculite, and hydrogen peroxide foaming process. By constructing a flame-retardant straw reinforcement, the mechanical strength and thermal insulation performance are improved.

Benefits of technology

A composite fireproof door core with excellent fire resistance and heat insulation properties, high mechanical strength and lightweight characteristics was prepared. It is highly impact-resistant, not easily damaged, and ensures fire safety and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121470889A_ABST
    Figure CN121470889A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite fireproof door core, and relates to the technical field of fireproof doors, and the preparation method comprises the following steps: at least carrying out calcium phosphate coating flame-retardant treatment on straw coarse crushed materials to obtain flame-retardant straws; the preparation method comprises the following steps: mixing sulphoaluminate cement, aluminate cement and fly ash according to a preset mass ratio to prepare cement-based powder; uniformly mixing flame-retardant straw, cement-based powder, expanded vermiculite and water, pouring hydrogen peroxide, and stirring to obtain a mixture; and pouring the mixture into a mold for self-foaming and curing, demolding, and curing at a preset temperature for at least 7 days to obtain the composite fireproof door core. The flame-retardant straw is obtained by at least carrying out calcium phosphate coating flame-retardant treatment on the straw coarse crushed material, and the flame-retardant straw is combined with the cement-based powder, the expanded vermiculite and the hydrogen peroxide foaming process, so that the composite fireproof door core with excellent fireproof and heat-insulating properties, high mechanical strength and light-weight characteristics is successfully prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fire door technology, and specifically to a method for preparing a composite fire door core. Background Technology

[0002] Fire doors prevent the spread of smoke and fire during a fire and are mainly installed at entrances to important rooms, fire-resistant partitions, evacuation routes, and pipe shafts. The fire door core, as the filling material, is crucial for maintaining the fire door's fire resistance, integrity, and insulation.

[0003] Currently, the research and development of fireproof door core materials has long faced a core contradiction: it is difficult to balance the material's lightweight nature with its strength and fire resistance. To achieve lightweight insulation, traditional materials such as perlite boards or foamed cement boards typically introduce a large number of pores, but this significantly sacrifices the material's mechanical strength, resulting in brittle finished products with poor impact resistance, making them prone to damage during transportation, installation, and use, thus affecting fire safety reliability. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art. This invention provides a method for preparing a composite fireproof door core. By at least treating coarsely crushed straw with calcium phosphate coating to obtain flame-retardant straw, and combining it with cement-based powder, expanded vermiculite and hydrogen peroxide foaming process, a composite fireproof door core with excellent fireproof and heat insulation performance, high mechanical strength and lightweight characteristics is successfully prepared.

[0005] This invention provides a method for preparing a composite fireproof door core, comprising the following steps: S1. At least the coarsely crushed straw is coated with calcium phosphate for flame retardant treatment to obtain flame retardant straw; S2. Sulfoaluminate cement, aluminate cement, and fly ash are mixed in a predetermined mass ratio to obtain cement-based powder. S3. By weight, take 5 to 15 parts of the flame-retardant straw, 1000 parts of the cement-based powder, 50 to 100 parts of expanded vermiculite and 581 to 724 parts of water, mix them evenly, then pour in 45 to 55 parts of hydrogen peroxide, and stir for 10 to 30 seconds to obtain the mixture. S4. Pour the mixture into a mold to self-foam and solidify. After demolding, place it in a preset temperature for curing for at least 7 days to obtain a composite fireproof door core.

[0006] Specifically, the calcium phosphate coating flame retardant treatment includes: The coarsely crushed straw was soaked in a calcium chloride solution for at least 24 hours and then filtered to obtain the first straw material. The first straw material was soaked in sodium phosphate solution for at least 2 hours and then filtered to obtain the second straw material. The second straw material is washed and dried to obtain the third straw material.

[0007] Specifically, step S1 includes: Flame-retardant straw was obtained by sequentially treating coarsely crushed straw with calcium phosphate coating, phosphorus-nitrogen intumescent flame retardant, and silica sol coating.

[0008] Specifically, the phosphorus-nitrogen intumescent flame retardant coating flame retardant treatment includes: The coarsely crushed straw that has undergone the calcium phosphate coating flame retardant treatment is immersed in a phosphorus-nitrogen intumescent flame retardant solution composed of pentaerythritol, ammonium polyphosphate and melamine for at least 24 hours, filtered and dried to obtain the fourth straw material. In the phosphorus-nitrogen intumescent flame retardant solution, the mass concentration of pentaerythritol ranges from 3.5% to 5.5%, the mass concentration of ammonium polyphosphate ranges from 10% to 12%, and the mass concentration of melamine ranges from 3.5% to 5.5%.

[0009] Specifically, the silica sol coating flame retardant treatment includes: The coarsely crushed straw material coated with the aforementioned phosphorus-nitrogen intumescent flame retardant was impregnated in silica sol with a pH of 8.5-10.5 and a solid content of 15%-30%. At the same time, 1%-3% of silane coupling agent by dry weight of silica sol was added. The mixture was stirred at 40℃-60℃ for 0.5h-2h, then filtered, and cured and dried at 100℃-140℃ for 0.5h-2h to obtain the fifth straw material.

[0010] Specifically, step S2 includes: Cement-based powder is prepared by mixing sulfoaluminate cement, aluminate cement, and fly ash in a mass ratio of (2~3):(2~3):1.

[0011] Specifically, in step S3, the expanded vermiculite undergoes a paraffin vacuum impregnation treatment.

[0012] Specifically, in step S3, the total amount of the flame-retardant straw, the cement-based powder, and the expanded vermiculite is m1, and the total amount of water is m2. Therefore: 0.55≤ ≤0.65.

[0013] Specifically, the mass concentration of the hydrogen peroxide ranges from 30% to 40%.

[0014] Specifically, after pouring the mixture into the mold, the mold is sealed with plastic wrap and demolded after at least 24 hours; after demolding, it is placed in an environment of 30℃~40℃ for at least 7 days to obtain a composite fireproof door core.

[0015] Compared with the prior art, the beneficial effects of the present invention are: The method for preparing the composite fireproof door core of this invention involves at least treating coarsely crushed straw with calcium phosphate coating to obtain flame-retardant straw. This flame-retardant straw does not become a flame propagation path or smoke source at high temperatures, meeting stringent fire safety standards. It can also serve as a fiber reinforcing phase to improve the brittleness of the composite fireproof door core, significantly enhancing its compressive, flexural, and impact resistance. The cement-based powder, prepared by mixing sulfoaluminate cement, aluminate cement, and fly ash in a predetermined mass ratio, provides a high-strength matrix, ensuring the mechanical strength of the composite fireproof door core. The addition of lightweight and heat-insulating expanded vermiculite effectively reduces the weight of the composite fireproof door core and improves its heat insulation performance. The hydrogen peroxide foaming process introduces closed pores, effectively reducing the density of the composite fireproof door core and resulting in a high degree of lightweighting.

[0016] In summary, by constructing a flame-retardant straw reinforcement and combining it with cement-based powder, expanded vermiculite, and hydrogen peroxide foaming process, a composite fireproof door core with excellent fireproof and heat insulation performance, high mechanical strength, and lightweight characteristics was successfully prepared. It is not easily broken, has strong impact resistance, and is not easily damaged during transportation, installation, and use, thus ensuring fire safety and reliability. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a schematic flowchart of the preparation method of the composite fireproof door core in an embodiment of the present invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] This invention provides a method for preparing a composite fireproof door core. Figure 1 A schematic flowchart of the preparation method of the composite fireproof door core in an embodiment of the present invention is shown, including the following steps: S1. At least the coarsely crushed straw is coated with calcium phosphate for flame retardant treatment to obtain flame retardant straw; Among them, the coarse straw crushed material consists of short filaments of 10mm to 50mm. After being coated with calcium phosphate for flame retardant treatment, it will not become a flame propagation path or smoke source at high temperatures, thus meeting strict fire protection standards. It can be used as a fiber reinforcing phase to improve the brittleness of the composite fireproof door core, significantly enhancing its compressive strength, flexural strength, and impact resistance.

[0021] In some specific embodiments, the calcium phosphate coating flame retardant treatment includes: First, the coarsely crushed straw is soaked in a calcium chloride solution for at least 24 hours and then filtered to obtain the first straw material. During the soaking process, the calcium chloride solution will fully penetrate the coarsely crushed straw, so that the coarsely crushed straw is fully loaded with calcium ions.

[0022] Next, the first straw material is immersed in a sodium phosphate solution for at least 2 hours and then filtered to obtain the second straw material. The sodium phosphate solution provides phosphate ions, and when the phosphate ions encounter the calcium ions loaded on the straw, a chemical reaction occurs, generating in-situ insoluble calcium phosphate salts, thus achieving comprehensive calcium phosphate coating of the coarsely crushed straw.

[0023] Finally, the second straw material is washed and dried to obtain the third straw material. Washing (water washing) can remove unreacted soluble salts (such as excess phosphate, chloride, sodium ions, etc.) remaining on the surface and pores of the straw, ensuring the purity of the final product; drying removes moisture, resulting in a stable "third straw material" that is convenient for subsequent processing and application.

[0024] Specifically, the mass concentration of the calcium chloride solution ranges from 5% to 10%, and the mass concentration of the sodium phosphate solution ranges from 2% to 8%. Optionally, the mass concentration of the calcium chloride solution is 5%, 7%, 9%, or 10%, and the mass concentration of the sodium phosphate solution is 2%, 4%, 6%, or 8%. Preferably, the mass concentration of the calcium chloride solution is 10%, and the mass concentration of the sodium phosphate solution is 8%, which results in a good impregnation effect and a thick calcium phosphate layer generated by the in-situ reaction.

[0025] In some specific embodiments, step S1 includes: sequentially subjecting the coarsely crushed straw to calcium phosphate coating flame retardant treatment, phosphorus-nitrogen intumescent flame retardant coating flame retardant treatment, and silica sol coating flame retardant treatment to obtain flame retardant straw.

[0026] Calcium phosphate coating flame retardant treatment can form an inorganic flame retardant barrier—a calcium phosphate layer—on the surface of coarsely crushed straw. It achieves a V-1 level in the vertical burning test (UL-94), laying a solid foundation for flame retardant straw.

[0027] The phosphorus-nitrogen intumescent flame retardant coating treatment can add a more advanced intumescent flame retardant layer on top of the inorganic flame retardant barrier. This intumescent flame retardant layer foams and expands when heated, forming a porous foam carbon layer with a density that is tens or even hundreds of times thicker than the calcium phosphate layer. This can provide efficient heat insulation and effectively delay temperature rise. Based on the calcium phosphate layer, a stable and solid base is provided for the expansion of the phosphorus-nitrogen intumescent flame retardant. The combination of the two produces a synergistic effect between the "thick inorganic layer" and the "expanded foam carbon layer", which significantly improves the flame retardant efficiency and heat insulation performance.

[0028] The silica sol coating flame retardant treatment can coat an additional layer of silica on top of the intumescent flame retardant layer. This silica layer will sinter at high temperature to form a strong network structure similar to ceramics. This can effectively enhance the strength of the "intumescent foam char layer", fix the structure of the "intumescent foam char layer" and improve the residual carbon rate, ensuring the structural integrity of the char layer and preventing "burn-through".

[0029] This "triple protection" system constructs a multi-stage, multi-mechanism defense system, ensuring that the vertical burning rating of flame-retardant straw does not end with "merely reaching V-1 level," but rather aims to "create a high-performance plant-based flame-retardant material that combines high strength, high efficiency, and long-lasting durability." Through precise process design, it achieves complementary advantages and synergistic effects of multiple functional materials, resulting in a comprehensive performance of the final flame-retardant straw product that far surpasses that of any single treatment.

[0030] Specifically, the phosphorus-nitrogen intumescent flame retardant coating flame retardant treatment includes: immersing coarsely crushed straw that has undergone the calcium phosphate coating flame retardant treatment in a phosphorus-nitrogen intumescent flame retardant solution composed of pentaerythritol, ammonium polyphosphate, and melamine for at least 24 hours, filtering, and drying to obtain a fourth straw material; in the phosphorus-nitrogen intumescent flame retardant solution, the mass concentration of pentaerythritol ranges from 3.5% to 5.5%, the mass concentration of ammonium polyphosphate ranges from 10% to 12%, and the mass concentration of melamine ranges from 3.5% to 5.5%.

[0031] Among them, pentaerythritol serves as the carbon source, providing char-forming substances and forming the basis for the foamed carbon layer; ammonium polyphosphate serves as the acid source, generating highly dehydrating polyphosphoric acid upon heating, catalyzing the dehydration and carbonization of pentaerythritol; melamine serves as the gas source, releasing a large amount of non-flammable gases (such as ammonia and nitrogen) upon thermal decomposition, causing the carbon layer to expand and foam; the three react at high temperatures, expanding on the material surface to form a porous and robust foamed carbon layer, which is an excellent thermal insulator and mass transfer barrier, and is the key to achieving high-efficiency flame retardancy.

[0032] Optionally, in the phosphorus-nitrogen intumescent flame retardant solution, the mass concentration of pentaerythritol can be 3.5%, 4%, 4.5%, 5%, or 5.5%, the mass concentration of ammonium polyphosphate can be 10%, 10.5%, 11%, 11.5%, or 12%, and the mass concentration of melamine can be 3.5%, 4%, 4.5%, 5%, or 5.5%. Preferably, the mass concentration of pentaerythritol is 4.5%, the mass concentration of ammonium polyphosphate is 11%, and the mass concentration of melamine is 4.5%. In this combination, the acid source, char source, and gas source achieve a near-ideal synergistic balance, which can form an expanded char layer with high structural strength and excellent heat insulation effect on the straw matrix, thereby giving the flame-retardant straw excellent flame retardant efficiency and heat insulation performance.

[0033] Furthermore, the silica sol coating flame retardant treatment includes: impregnating the coarsely crushed straw material coated with the phosphorus-nitrogen intumescent flame retardant into a silica sol with a pH of 8.5-10.5 and a solid content of 15%-30%, while simultaneously adding 1%-3% of silane coupling agent by dry weight of the silica sol, stirring at 40℃-60℃ for 0.5h-2h, then filtering, and curing and drying at 100℃-140℃ for 0.5h-2h to obtain the fifth straw material.

[0034] Silica sol (pH 8.5~10.5, solid content 15%~30%) creates an alkaline environment within its pH range, ensuring the stability of the silica nanoparticles and preventing premature gelation, thus guaranteeing uniform penetration and coating by the treatment solution. Optionally, the pH of the silica sol can be 8.5, 9, 9.5, 10, or 10.5. Its solid content range represents an optimized concentration; if the solid content is too low, the formed silica layer will be too thin and its performance insufficient; if the solid content is too high, the solution will be viscous, affecting penetration and dispersion, and easily causing uneven coating. This solid content range ensures both the thickness of the silica layer and good processability. Optionally, the solid content of the silica sol can be 15%, 20%, 25%, or 30%.

[0035] The silane coupling agent (1%~3% of the dry basis of the silica sol) greatly enhances the chemical bonding and adhesion between the silica layer and the intumescent flame retardant layer, making the silica layer less prone to peeling and flaking, achieving a leap from "physical coating" to "chemical bonding"; optionally, the silane coupling agent can be 1%, 2%, or 3% of the dry basis of the silica sol.

[0036] Treatment conditions (stirring at 40℃~60℃ for 0.5h~2h): Moderate heating helps accelerate the hydrolysis of the silane coupling agent and its reaction with the intumescent flame-retardant layer, improving treatment efficiency; stirring ensures sufficient and uniform contact between the intumescent flame-retardant layer and the silica sol on the straw substrate, resulting in a consistent coating thickness. Optionally, treatment can be carried out at 40℃ for 2h, at 50℃ for 1h, or at 60℃ for 0.5h.

[0037] Curing and drying (drying at 100℃~140℃ for 0.5h~2h) serves two purposes: removing moisture and completing the final curing of the silica layer. At 100℃~140℃, the silica nanoparticles in the silica sol partially sinter and fuse, forming a continuous, dense, and robust inorganic-organic hybrid network structure with the silane coupling agent. This network firmly anchors the intumescent flame-retardant layer onto the straw substrate. This inorganic-organic hybrid network structure securely "locks" the internal intumescent flame-retardant layer to the straw substrate, preventing it from being lost due to migration, moisture absorption, or physical friction, thus ensuring the long-term effectiveness of the flame-retardant effect. Furthermore, at high temperatures, this inorganic-organic hybrid network structure provides a rigid framework for the intumescent foam char layer, effectively enhancing its strength, fixing its structure, and increasing the residual char rate, ensuring the structural integrity of the char layer and preventing burn-through. Optionally, the product can be dried at 100°C for 2 hours, at 120°C for 1 hour, or at 140°C for 0.5 hours.

[0038] S2. Sulfoaluminate cement, aluminate cement, and fly ash are mixed in a predetermined mass ratio to obtain cement-based powder. Cement-based powder, prepared by mixing sulfoaluminate cement, aluminate cement, and fly ash in a predetermined mass ratio, can provide a high-strength matrix, ensuring the mechanical strength of the composite fireproof door core.

[0039] Specifically, sulfoaluminate cement, aluminate cement, and fly ash are mixed in a mass ratio of (2~3):(2~3):1 to obtain cement-based powder.

[0040] Among them, sulfoaluminate cement has the characteristics of rapid hardening, early strength, micro-expansion, and high temperature resistance, which enables the composite fireproof door core board to have sufficient mechanical strength in the early stages of demolding and curing, thus improving production efficiency. Moreover, the micro-expansion characteristics of sulfoaluminate cement can offset the drying shrinkage and chemical shrinkage generated during the hydration process of other components, effectively preventing the core board from cracking. This is the key to ensuring the dimensional stability and appearance quality of composite fireproof door core products. In addition, sulfoaluminate cement can maintain a certain structural strength at high temperatures.

[0041] Aluminate cement possesses high strength and high-temperature resistance, providing final strength and a fire-resistant framework in cement-based systems. Under fire conditions, aluminate cement reacts with other components to form a robust ceramic bond, maintaining the overall structure of the door core panel and preventing burn-through. Furthermore, aluminate cement can synergistically work with sulfoaluminate cement to further optimize the system's setting and hardening rate.

[0042] Fly ash possesses pozzolanic activity and morphological effects (microbead lubrication), and is inexpensive. The fine particles of fly ash effectively fill the voids between cement particles, making the hardened body more compact, thereby increasing strength and reducing permeability. Furthermore, the slow pozzolanic reaction of fly ash allows for continuous consumption of hydration products, significantly enhancing the long-term strength of the system. Additionally, fly ash particles act as a lubricant, improving slurry flow and making it easier to mix evenly with flame-retardant straw. Moreover, using fly ash can effectively reduce material costs and achieve the resource utilization of industrial by-products.

[0043] The preset mass ratio is (2~3):(2~3):1, with sulfoaluminate cement and aluminate cement as the main components (2~3). This ensures that the system has sufficient early and late strength, as well as excellent refractory properties. The ratio between sulfoaluminate cement and aluminate cement fluctuates around 1:1, allowing for fine-tuning according to specific strength development requirements and costs. Fly ash is an important auxiliary material, with a fixed proportion of 1. As a benchmark, this proportion can fully utilize its positive effects of filling, densifying, and improving workability, while avoiding the problem of excessive addition leading to low early strength.

[0044] Preferably, sulfoaluminate cement, aluminate cement, and fly ash are mixed in a mass ratio of 2.5:2.5:1 to prepare cement-based powder, which effectively balances multiple objectives such as rapid hardening, high strength, fire resistance, and economy.

[0045] S3. By weight, take 5 to 15 parts of the flame-retardant straw, 1000 parts of the cement-based powder, 50 to 100 parts of expanded vermiculite and 581 to 724 parts of water, mix them evenly, then pour in 45 to 55 parts of hydrogen peroxide, and stir for 10 to 30 seconds to obtain the mixture. First, mix a specific weight proportion of flame-retardant straw, cement-based powder, expanded vermiculite and water evenly, then pour in a specific weight proportion of hydrogen peroxide and stir briefly and quickly to obtain a mixture to be self-foaming and curing.

[0046] Among them, cement-based powder (1000 parts) is the absolute main body of the system, providing the final mechanical strength and refractory skeleton, and the dosage of all other components is based on it.

[0047] Water (581-724 parts) serves two purposes: firstly, it ensures the cement is fully hydrated and gives the slurry sufficient consistency to "capture" the air bubbles generated by the subsequent hydrogen peroxide, forming a stable foam structure; secondly, it ensures the slurry has good fluidity, making it easy to mix quickly and evenly with other components and to be successfully cast into shape.

[0048] Flame-retardant straw (5 to 15 parts) is used as a flame-retardant organic fiber filler. When dispersed in the cement matrix, it can inhibit the cracking of the cement paste and improve the brittleness of the composite fireproof door core, thus significantly improving its compressive strength, flexural strength and impact resistance.

[0049] Expanded vermiculite (50-100 parts) is an ultralight refractory filler filled with air, making it an excellent lightweight, heat-insulating, and high-temperature resistant material. In the system, it further reduces the density and weight of the door core panel and significantly improves its high-temperature heat insulation performance, forming a synergy with the flame-retardant effect of the cement matrix.

[0050] Hydrogen peroxide (45-55 parts) decomposes rapidly in cement paste, producing countless tiny oxygen bubbles. These tiny oxygen bubbles are encapsulated in the dense cement paste, thus forming a uniform closed-cell foam concrete structure after overall curing. This effectively reduces the density of the composite fireproof door core and results in a high degree of lightweighting.

[0051] Specifically, first, cement-based powder and expanded vermiculite are mixed evenly to obtain a solid mixture; then, flame-retardant straw is dispersed and suspended in water to obtain a suspension; next, the suspension is poured into the solid mixture and stirred evenly to obtain a slurry; finally, hydrogen peroxide is poured into the slurry and briefly and rapidly stirred to obtain a mixture to be self-foaming and curing. The brief, rapid stirring allows the hydrogen peroxide to be quickly and evenly dispersed throughout the slurry system, but does not allow it too much time to begin decomposition; subsequently, it is immediately poured into a mold for self-foaming and curing.

[0052] Preferably, by weight, 5 parts of the flame-retardant straw, 1000 parts of the cement-based powder, 100 parts of expanded vermiculite, and 608 parts of water are mixed evenly, and then 50 parts of hydrogen peroxide are added and stirred for 10 seconds to obtain a mixture. The resulting composite fireproof door core has excellent performance, is lightweight, high-strength, and has excellent fire resistance.

[0053] In some specific embodiments, cement-based powder, expanded vermiculite, and calcium stearate are mixed evenly to obtain a solid mixture. Calcium stearate plays a key role as a physical foaming stabilizer in the mixture. It can adhere to the interface of the bubble film, significantly enhancing the mechanical strength and elasticity of the bubble film, thereby slowing down the rate of bubble breakage and merging, making the foam system more stable. Moreover, calcium stearate can reduce the rate of liquid drainage between bubbles, buying valuable time for cement to set and solidify, so that the foam structure can be well fixed.

[0054] Specifically, the amount of calcium stearate used is 1% to 2% of the mass of cement-based powder, preferably 1.5%. Premixing cement-based powder, expanded vermiculite and calcium stearate provides an ideal physical environment for the subsequent hydrogen peroxide foaming process, ensuring that the final door core panel has a uniform, stable and excellent closed pore structure, which is conducive to achieving a perfect combination of lightweight, high strength and heat insulation.

[0055] In some specific embodiments, the expanded vermiculite undergoes a paraffin vacuum impregnation treatment. Expanded vermiculite itself possesses extremely excellent thermal insulation properties, thanks to its porous, layered structure; however, these abundant pores are also its biggest drawback: it absorbs moisture rapidly like a sponge, even absorbing humidity from the environment. When vermiculite containing a large amount of moisture is used in door panels, it brings several problems: for example, increasing the weight of the door panel and reducing thermal insulation performance (water has a much higher thermal conductivity than air). By performing a paraffin vacuum impregnation treatment on the expanded vermiculite, these problems can be effectively solved.

[0056] Specifically, the expanded vermiculite is placed in a vacuum environment to completely remove the air from its pores. While maintaining the vacuum, molten liquid paraffin is introduced. Due to the negative pressure inside the expanded vermiculite, the liquid paraffin is forcefully drawn in and fills every tiny pore. After being removed and cooled, the paraffin solidifies inside the pores, forming a solid state.

[0057] After treatment, paraffin wax is evenly coated on the surface and internal pore walls of each expanded vermiculite layer. Paraffin wax itself is highly hydrophobic, ensuring that the treated expanded vermiculite does not absorb water or moisture. This allows the door core panel to maintain dryness, lightness, and stable thermal insulation performance even in humid environments, significantly extending its service life. Furthermore, the paraffin wax fills the pores, replacing the air or water vapor that would otherwise have entered. While paraffin wax has a higher thermal conductivity than static air, it is far lower than water, still allowing the expanded vermiculite to maintain good thermal insulation performance. More importantly, paraffin wax is a phase change material; it absorbs a large amount of heat when it melts (latent heat of phase change). In the event of a fire, this paraffin wax absorbs heat and melts, not only slowing heat transfer to the back of the door but also helping to lower the system temperature, providing additional "heat-absorbing" fire resistance. In addition, untreated expanded vermiculite instantly absorbs moisture from cement paste, affecting normal cement hydration. However, the paraffin-coated expanded vermiculite no longer absorbs water, ensuring the workability of the cement paste and the normal progress of the hydration process.

[0058] In some specific embodiments, the total amount of the flame-retardant straw, the cement-based powder, and the expanded vermiculite is m1, and the total amount of water is m2. Then: 0.55≤ ≤0.65.

[0059] The required water-cement ratio is 0.55 to 0.65. The lower limit (0.55) ensures sufficient cement hydration and gives the slurry enough consistency to trap air bubbles generated by hydrogen peroxide, forming a stable foam structure. The upper limit (0.65) ensures good slurry fluidity, facilitating rapid and uniform mixing with other components and smooth casting. Optionally, the water-cement ratio can be 0.55, 0.60, or 0.65; preferably, a water-cement ratio of 0.55 results in a composite fireproof door core with excellent overall performance.

[0060] In some specific embodiments, the mass concentration of hydrogen peroxide ranges from 30% to 40%. Below 30%, the gas production of hydrogen peroxide is insufficient to fully foam the dense cement paste, making it difficult to achieve the ultra-low density required for the core panel. A concentration of 30% is an effective starting point; the decomposition reaction rate at this concentration is fast enough to match the cement setting time well, ensuring that most of the foaming process is completed before the paste hardens, thus ensuring the formation of significant porosity. The upper limit of hydrogen peroxide concentration (40%) is the boundary between safety and controllability. The higher the hydrogen peroxide concentration, the more vigorous the decomposition reaction and the more heat is released. Above 40%, the reaction becomes too rapid, easily leading to bubble coalescence and even the collapse of the core panel structure.

[0061] Optionally, the mass concentration of the hydrogen peroxide can be 30%, 32%, 34%, 36%, 38%, or 40%; preferably, the mass concentration of the hydrogen peroxide is 34%, which fully utilizes the foaming efficiency of high-concentration hydrogen peroxide while minimizing the potential process risks.

[0062] S4. Pour the mixture into a mold to self-foam and solidify. After demolding, place it in a preset temperature for curing for at least 7 days to obtain a composite fireproof door core.

[0063] The mixture containing hydrogen peroxide is quickly poured into the mold. At this time, the hydrogen peroxide reacts violently with the alkaline substances in the cement paste, producing a large amount of oxygen. Since the mixture is adhered to by the dense paste, these gases cannot escape and form countless tiny bubbles inside, causing the entire mixture to expand rapidly and fill the mold. The time from pouring to initial solidification is crucial. The environment must be kept stable, and any vibration or movement must be avoided, otherwise the fragile foam structure will be damaged, leading to mold collapse or uneven pore structure.

[0064] Allow the foam-filled mold to stand at room temperature until the cement paste has initially set and hardened, achieving sufficient "early strength," before demolding. Sulfoaluminate cement exhibits its "rapid hardening and early strength" characteristics here, significantly shortening demolding time and improving mold turnover and production efficiency.

[0065] After demolding, the cement is cured at a preset temperature for at least 7 days, which helps to ensure full hydration of the cement, develop its final strength, and improve its durability, so that the cement matrix can achieve its excellent mechanical properties. Finally, the stable foam structure and fully hydrated cement stone, together with the internal flame-retardant straw and expanded vermiculite, constitute the final solid, porous, and efficient fireproof and heat-insulating body.

[0066] Specifically, after pouring the mixture into the mold, the mold is sealed with plastic wrap and demolded after at least 24 hours; after demolding, it is placed in an environment of 30℃~40℃ for at least 7 days to obtain a composite fireproof door core.

[0067] Sealing the mold with plastic wrap can effectively prevent moisture evaporation and protect the cement hydration reaction process. On the other hand, it can effectively ensure that the gas and heat generated by the decomposition of hydrogen peroxide are retained inside, which helps to form and stabilize the internal foam structure and prevents it from collapsing due to external airflow and other factors.

[0068] Demolding should be carried out after at least 24 hours to allow sufficient time for early strength development. Although sulfoaluminate cement has rapid hardening properties, the overall structural strength needs time to develop in this complex foaming system. 24 hours is a safe and sufficient resting period to ensure that the foamed cement body has sufficient "skeleton strength" to resist the stress generated during demolding and avoid deformation or damage. Moreover, the demolding time should not only take into account the setting of cement but also the stability of the entire foaming system. The 24-hour setting ensures that the three processes of foaming, setting, and strength development are basically completed simultaneously, and the product has been transformed from a "slurry" into a "board".

[0069] Curing at 30℃~40℃ for at least 7 days accelerates and optimizes performance. The cement hydration reaction rate increases significantly with temperature; curing at 30℃~40℃ allows the 7-day strength to approach or reach the strength level of 28 days under standard conditions at 20℃, greatly shortening the production cycle and improving efficiency. Furthermore, appropriate heat curing promotes more complete hydration, generating more hydration products and making the cement stone structure denser. This not only improves the final mechanical strength but also enhances the material's durability and impermeability. In addition, providing a stable and controllable temperature environment ensures that each batch and each core panel undergoes the exact same curing process, resulting in extremely stable and uniform product quality. Optionally, curing can be done at 30℃, 35℃, or 40℃ for at least 7 days; preferably, curing at 35℃ for at least 7 days maximizes the material's performance potential while ensuring production stability, economy, and product quality uniformity.

[0070] The composite fireproof door core prepared by the method of this invention has a microstructure in which cement stone serves as a continuous matrix, with expanded vermiculite uniformly distributed within it. The continuous matrix is ​​filled with uniformly distributed closed-cell air bubbles generated by hydrogen peroxide, and flame-retardant straw fibers act as reinforcing ribs throughout. In terms of macroscopic properties, the composite fireproof door core has extremely low density, thanks to the foaming effect of hydrogen peroxide, resulting in a density far lower than traditional cement products. Furthermore, the composite fireproof door core possesses extremely high strength; the cement matrix and flame-retardant straw fibers provide high mechanical strength on a lightweight basis. In addition, the composite fireproof door core exhibits excellent fire resistance, integrating the inorganic non-combustible properties of cement, the superior thermal insulation of expanded vermiculite, and the multiple flame-retardant properties of flame-retardant straw, achieving multiple layers of protection. Moreover, the composite fireproof door core has good sound insulation and thermal insulation properties; its porous structure itself is an excellent acoustic and thermal insulator.

[0071] In summary, by constructing a flame-retardant straw reinforcement and combining it with cement-based powder, expanded vermiculite, and hydrogen peroxide foaming process, a composite fireproof door core with excellent fireproof and heat insulation performance, high mechanical strength, and lightweight characteristics was successfully prepared. It is not easily broken, has strong impact resistance, and is not easily damaged during transportation, installation, and use, thus ensuring fire safety and reliability.

[0072] Flame retardant test of straw materials 1. Untreated, coarsely crushed straw.

[0073] (1) Thermal decomposition behavior: Thermogravimetric analysis showed that the thermal decomposition curve of untreated straw coarse crushed material had multiple weight loss stages, corresponding to the decomposition of different components in the straw coarse crushed material; the initial thermal decomposition temperature (5% weight loss) was about 200℃, the main decomposition stage was between 200℃ and 350℃ (decomposition of hemicellulose and cellulose), and the termination thermal decomposition temperature (95% weight loss) was about 500℃; the char residue (at 600℃) was low, about 10% to 15%.

[0074] (2) Combustion performance: The limiting oxygen index (LOI) is about 18%, which is a flammable material; in the vertical burning test (UL-94), the material burns rapidly for more than 30 seconds and is accompanied by dripping, and is rated as No rating (NR).

[0075] 2. Coating coarsely crushed straw with calcium phosphate for flame retardancy treatment to obtain first-grade flame-retardant straw.

[0076] (1) Thermal decomposition behavior: Thermogravimetric analysis showed that the thermal decomposition of the first-stage flame-retardant straw was only one stage, with an initial thermal decomposition temperature (5% weight loss) of approximately 210℃ and a final thermal decomposition temperature (95% weight loss) of approximately 380℃. This indicates that calcium phosphate coating promoted the formation of a uniform char layer and inhibited multi-stage decomposition. The char residue (at 600℃) increased to approximately 25%~30%.

[0077] (2) Combustion performance: The limiting oxygen index (LOI) is increased to about 24%, which is a self-extinguishing material; in the vertical burning test (UL-94), the self-extinguishing time is shortened to 10 to 15 seconds, with no dripping phenomenon, and the rating reaches V-1 level.

[0078] 3. The coarsely crushed straw is sequentially treated with calcium phosphate coating flame retardant treatment, phosphorus-nitrogen intumescent flame retardant coating flame retardant treatment, and silica sol coating flame retardant treatment to obtain the second flame-retardant straw.

[0079] (1) Thermal decomposition behavior: Thermogravimetric analysis showed that the thermal decomposition curve of the second flame-retardant straw was more stable, with an initial thermal decomposition temperature (5% weight loss) of about 250℃ and a final thermal decomposition temperature (95% weight loss) of about 400℃. The char residue (at 600℃) increased significantly, reaching 40%~45%, which is due to the formation of an expanded char layer by the phosphorus-nitrogen intumescent flame retardant during heating, and the silica sol further reinforced the char layer, improving thermal stability.

[0080] (2) Combustion performance: The limiting oxygen index (LOI) is further improved to about 30%, which is classified as a flame-retardant material; in the vertical burning test (UL-94), the material self-extinguishes immediately after being removed from the flame, the burning time is less than 5 seconds, there is no dripping phenomenon, and the rating reaches V-0 level.

[0081] Performance comparison of door core panels 1. Traditional door core panel materials: The density range of perlite boards is 200 kg / m³. 3 ~350kg / m 3 Its compressive strength ranges from 0.5MPa to 1.5MPa, but its flexural strength is low and it is easy to break. Its thermal conductivity ranges from 0.06W / (m·K) to 0.09W / (m·K), and it is brittle and easily crushed upon impact.

[0082] The density range of foamed cement board is 200 kg / m³. 3 ~400kg / m 3 Its compressive strength ranges from 0.5MPa to 2.0MPa, but its flexural strength is low and it is easy to break. Its thermal conductivity ranges from 0.07W / (m·K) to 0.12W / (m·K), and it is brittle and easily crushed by impact.

[0083] 2. Panel material of composite fireproof door core: Using 1000g of cement-based powder as a benchmark, and taking the expanded vermiculite content, water-cement ratio, 30% hydrogen peroxide content, and flame-retardant straw content as four factors in Table 1, a four-factor, three-level orthogonal test table was designed to test and obtain the performance parameters of the composite fireproof door core.

[0084]

[0085] Result: The density range of the composite fireproof door core of the present invention is 350 kg / m³. 3 ~550kg / m 3 (Adjustable), achieving lightweight design, effectively reducing the weight of the door core panel and facilitating installation; compressive strength ≥2.5MPa (up to 4.0MPa or more), compared to traditional door core panel materials, the strength is increased by 100%~400%, fundamentally solving the problem of fragility; flexural strength ≥1.5MPa, giving the material excellent bending and impact resistance; thermal conductivity range of 0.08W / (m·K)~0.12W / (m·K), maintaining excellent heat insulation performance and meeting the core requirements for fireproof and heat insulation; high toughness, not easy to break, solving the problem of damage during transportation, installation and use, reducing losses.

[0086] Furthermore, the non-combustibility test results of the composite fireproof door core of the present invention show that the furnace temperature rise is <30°C and the mass loss rate is <50%; the calorific value test results show that the calorific value is <2.0 MJ·kg. -1 Its combustion performance reaches Class A level (non-combustible).

[0087] The preparation method of a composite fireproof door core provided by the embodiments of the present invention has been described in detail above. Specific examples have been used to illustrate the principle and implementation of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation and application scope based on the idea of ​​the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A method for preparing a composite fireproof door core, characterized in that, Includes the following steps: S1. At least the coarsely crushed straw is coated with calcium phosphate for flame retardant treatment to obtain flame retardant straw; S2. Sulfoaluminate cement, aluminate cement, and fly ash are mixed in a predetermined mass ratio to obtain cement-based powder. S3. By weight, take 5 to 15 parts of the flame-retardant straw, 1000 parts of the cement-based powder, 50 to 100 parts of expanded vermiculite and 581 to 724 parts of water, mix them evenly, then pour in 45 to 55 parts of hydrogen peroxide, and stir for 10 to 30 seconds to obtain the mixture. S4. Pour the mixture into a mold to self-foam and solidify. After demolding, place it in a preset temperature for curing for at least 7 days to obtain a composite fireproof door core.

2. The method for preparing the composite fireproof door core as described in claim 1, characterized in that, The calcium phosphate coating flame retardant treatment includes: The coarsely crushed straw was soaked in a calcium chloride solution for at least 24 hours and then filtered to obtain the first straw material. The first straw material was soaked in sodium phosphate solution for at least 2 hours and then filtered to obtain the second straw material. The second straw material is washed and dried to obtain the third straw material.

3. The method for preparing the composite fireproof door core as described in claim 1, characterized in that, Step S1 includes: Flame-retardant straw was obtained by sequentially treating coarsely crushed straw with calcium phosphate coating, phosphorus-nitrogen intumescent flame retardant, and silica sol coating.

4. The method for preparing the composite fireproof door core as described in claim 3, characterized in that, The phosphorus-nitrogen based intumescent flame retardant coating flame retardant treatment includes: The coarsely crushed straw that has undergone the calcium phosphate coating flame retardant treatment is immersed in a phosphorus-nitrogen intumescent flame retardant solution composed of pentaerythritol, ammonium polyphosphate and melamine for at least 24 hours, filtered and dried to obtain the fourth straw material. In the phosphorus-nitrogen intumescent flame retardant solution, the mass concentration of pentaerythritol ranges from 3.5% to 5.5%, the mass concentration of ammonium polyphosphate ranges from 10% to 12%, and the mass concentration of melamine ranges from 3.5% to 5.5%.

5. The method for preparing the composite fireproof door core as described in claim 3, characterized in that, The silica sol coating flame retardant treatment includes: The coarsely crushed straw material coated with the aforementioned phosphorus-nitrogen intumescent flame retardant was impregnated in silica sol with a pH of 8.5-10.5 and a solid content of 15%-30%. At the same time, 1%-3% of silane coupling agent by dry weight of silica sol was added. The mixture was stirred at 40℃-60℃ for 0.5h-2h, then filtered, and cured and dried at 100℃-140℃ for 0.5h-2h to obtain the fifth straw material.

6. The method for preparing the composite fireproof door core as described in claim 1, characterized in that, Step S2 includes: Cement-based powder is prepared by mixing sulfoaluminate cement, aluminate cement, and fly ash in a mass ratio of (2~3):(2~3):

1.

7. The method for preparing the composite fireproof door core as described in claim 1, characterized in that, In step S3, the expanded vermiculite is subjected to a paraffin vacuum impregnation treatment.

8. The method for preparing the composite fireproof door core as described in claim 1, characterized in that, In step S3, the total amount of the flame-retardant straw, the cement-based powder, and the expanded vermiculite is m1, and the total amount of water is m2. Therefore: 0.55≤ ≤0.65。 9. The method for preparing the composite fireproof door core as described in claim 1, characterized in that, The mass concentration of the hydrogen peroxide is in the range of 30% to 40%.

10. The method for preparing the composite fireproof door core as described in claim 1, characterized in that, After pouring the mixture into the mold, seal the mold with plastic wrap and demold after at least 24 hours. After demolding, place it in an environment of 30℃~40℃ for at least 7 days to obtain a composite fireproof door core.